Kriteria Penentu Kunjungan Wisatawan Pada Objek Wisata Alam di Kabupaten Balangan - Helwani, Akhmad Syarif; Rudiansyah (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2022)
This study aims to determine the effect of the variable gross regional domestic product, several unemployment, regional minimum wages, consumer price index, and population on the number of poverty in South Kalimantan Province simultaneously and partially and what variables are the most dominant. This study uses secondary data over 20 years (2000-2019) with multiple linear regression analysis tools. The results showed all independent variables simultaneously; Gross regional domestic product, total unemployment, regional minimum wages, consumer price index, and population have a significant partially effect on the number of poor people. It is known that the number of unemployed and total population variables have a considerable impact and show a positive relationship to the number of poor people has a substantial and negative effect on the number of poor people. The most dominant variable influencing the number of poor people in South Kalimantan Province is population.